Motor Nonlinearities in Electrodynamic Loudspeakers: Modelling and Measurement - MERIT, Benoit; LEMARQUAND, Valérie; LEMARQUAND, Guy; DOBRUCKI, Andrzej (Archives of Acoustics, 2009)
This paper studies the motor nonlinearities of a classical electrodynamic loudspeaker. Measurements show the dependence of the voice-coil inductance with its position and with the driving current as well as the force factor dependence on the coil position. They allow the tuning of the parameters of a model proposed for these dependences. Time and frequency analysis of the model help in the explanation of both the harmonic and intermodulation distortions observed in classical loudspeakers.